Mediators of ethical leadership and group performance outcomes. Issue 7 (4th October 2017) - Peng, J.C.; Lin, Julian
Abstract : Purpose: The purpose of this paper is to examine the relationship between ethical leadership and group-level performance outcomes and show that group value congruence and group trust play pivotal mediating roles in the relationship between ethical leadership and work group performance outcomes. Design/methodology/approach: To examine the proposed model, survey data from 116 branches of a baked goods and beverages chain located in Northern Taiwan were analyzed. Findings: The results revealed that ethical leadership was positively and significantly related to group in-role performance and group helping behavior; the relationship was fully mediated by group value congruence and group trust after controlling for idealized influence leadership. Research limitations/implications: This study features a cross-sectional study design, thus limiting the accuracy of inferences about causality. Practical implications: The results of the current study revealed that ethical leadership behaviors enhance group trust. Hence, these leadership behaviors could be among the best and most appropriate practices to be implemented in China and Taiwan. Originality/value: The data suggested that ethical leadership was associated with not only individual-level behavior but also group-level performance. Furthermore, this paper also uncovered the mediation mechanism through which ethical leadership enhances group performance.